Pengaruh Profitabilitas, Likuditas, dan Struktur Aktiva terhadap Struktur Modal (Studi Kasus pada Perusahaan Manufaktur Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2018-2019) - Sri Rosmawati; Sinta Anggraini (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT STIE-GRAHA KARYA MUARA BULIAN, 2021)
The goal of the company is to get the maximum profit. To obtain maximum profit, the company's management must implement appropriate financial decisions, whether investment decisions, funding decisions or dividend decisions. With the right decisions, of course the achievement of company goals will be realized. Food and beverage companies are one of the industrial sector categories on the Indonesia Stock Exchange (IDX) which have the ability to continue to exist in the current economic conditions. Even during the pandemic, which occurred in early 2020 in Indonesia, this industry was one of the industries that was able to survive in the midst of the economic crisis that hit almost the entire world. The purpose of this study was to measure the effect of Profitability, Liquidity, and Asset Structure on Capital Structure in Food and Beverage Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2018-2019 Period. From the research results, it is known that Profitability, Liquidity and Asset Structure simultaneously affect the Capital Structure. Profitability has no significant and positive effect on capital structure, while liquidity and asset structure have no significant and negative effect on capital structure. Adjusted R-squared of 0.655714 shows that variations in changes in independent variables (Profitability, Liquidity, and Asset Structure) can explain changes in the dependent variable (Capital Structure) of 65.58%, while the remaining 34.42% is explained by other variables that not in the model.